1999
DOI: 10.21236/ada368034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Angle-Ply Orientation on Compression Strength of Composite Laminates

Abstract: March 1999This is a preprint of a paper intended for publication in a journal or proceedings. Since changes may be made before publication, this preprint is made available with the understanding that it will not be cited or reproduced without the permission of the author. PREPRINT Effect of Angle-Ply Orientation on Compression Strength of Composite LaminatesChristopher P. R. Hoppel This work has implications in the selection of composite failure criterion for compression performance, design of test coupons fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…where i,j f g 1, 2, 3 f g and k 1, 2, …,N lamina f g . In Equations (2)(3)(4), the position within the laminate, x 3,k is shown in Figure 1A. The stiffness matrix is then inverted to form the compliance matrix as…”
Section: Effective Stiffness and Failure Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…where i,j f g 1, 2, 3 f g and k 1, 2, …,N lamina f g . In Equations (2)(3)(4), the position within the laminate, x 3,k is shown in Figure 1A. The stiffness matrix is then inverted to form the compliance matrix as…”
Section: Effective Stiffness and Failure Criteriamentioning
confidence: 99%
“…The mechanical and structural characteristics of a laminate is highly influenced by ply orientation. According to the layup, a given lamina in a laminate can produce compressive strain for a given load, whereas a laminate with a different layup can have individual lamina that produce both tensile and compressive strains as demonstrated by Hoppel and Teresa 3 . Considerable research has been conducted to measure or otherwise determine the ply orientation of a manufactured part.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend was also found in Hoppel and De Teresa. 46 Shallow angle effect on static strengths of BX, TA, TX. The static tensile strengths X T of BX, TA, and TX were measured and predicted, as summarized in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…A review of these models was presented and compared [4] and it showed once again that Rosen's model was found to be overestimating the experimental data. Since fiber alignment plays a dominant factor in determining the compressive strength of unidirectional composites, several researches have been conducted to study this factor, such as the effect of angleply orientation [5], random fiber waviness [6] and the effect of fiber waviness on the compressive strength of unidirectional carbon fiber composites [7]. It showed [5] that specimens with the [0/±30] architecture had both the highest Poisson's ration and the lowest calculated ply-level compression strength.…”
Section: Introductionmentioning
confidence: 99%